ANALYSIS THE INFLUENCE OF ORGANIZATIONAL CULTURE: POWER DISTANCE, INDIVIDUALISM AND MASCULINITY TO EMPLOYEE PERFORMANCE AT PT. FREEPORT INDONESIA - Sumarauw, Beauty; Saerang, David Paul Elia; Pandowo, Merinda (Universitas Sam Ratulangi, 2014)
Human resource is a major asset in an organization. Organizations should have its own personalities, which are reflected in their organizational culture. The activities in the organization will not work properly without the involvement of human element; meanwhile the success of achieving organizational goals is supported entirely from the behavior of employees. The external forces may suggest the need of cultural change therefore the culture of the organization will be formed in accordance with the strategy and its environment. This research is aimed to analyze (1) do power distance, individualism, masculinity influence employee performance at Quality Management Service (QMS) Department, PT. Freeport Indonesia; (2) which of power distance, individualism, masculinity has significant influence on employee performance at QMS Department, PT. Freeport Indonesia. The research methodology is associated with multiple linear regression analysis technique, as sample of the research 100 respondents. The findings revealed that power distance, individualism and masculinity have a significant effect to the employee performance at QMS Department. Masculinity is the most influencing factor on employee performance. In overall, PT Freeport Indonesia, particularly in QMS department should keep and maintain a work environment with regard to the personal values ​​and employee personality in line with organizational culture to maximize their performance. Keywords: power distance, individualism, masculinity, employee performance.